A salt lake under stress: Relationships among birds, water levels, and invertebrates at a Great Basin saline lake. (April 2018) - Senner, Nathan R.; Moore, Johnnie N.; Seager, S. Trent; Dougill, Steve; Kreuz, Keith; Senner, Stanley E.
Abstract: Saline lakes are threatened globally and provide critical habitat for a diverse array of migratory and breeding waterbirds. The ability of large numbers of waterbirds to profitably use saline lakes is primarily dependent upon concentrations of invertebrate fauna that are only present within a narrow range of salinities. Additionally, waterbirds themselves can incur steep physiological costs as their salt loads increase, meaning that they are especially sensitive to changes in salinity. Nonetheless, relatively little is known about ecosystem function within natural saline lakes or how birds will respond to fluctuations in salinity across time, hindering efforts to maintain ecologically functional saline ecosystems. To help address this gap, we coupled data from waterbird surveys undertaken across 25 years at Lake Abert, Oregon, USA with data on lake area (a proxy for salinity) and invertebrate abundance to document how waterbird numbers changed in response to variation in lake area and the presence of their invertebrate prey. We found that as the area of Lake Abert decreased and salinity increased, both invertebrate and waterbird numbers declined, with especially high salinities associated with the presence of few waterbirds and invertebrates. However, we also found that at high lake levels and low salinities the abundance of most waterbirds and invertebrates either plateaued or declined as well. Our study reinforces physiological studies showing that both invertebrates and waterbirds can only tolerate a narrow range of salinities, and is among the first to document the effects of this tolerance range at the ecosystem level. As anthropogenic water usage increases and snowfall decreases in the coming century, Great Basin saline lakes are projected to increasingly face water shortages and high salinities. Conserving saline lake ecosystems thus requires mitigating these losses and maintaining water levels and salinities within the normal range of inter-annual variation. When conditions outside of this range occur too frequently or persist too long, they can result in dysfunctional ecosystems with deleterious consequences for the species that rely on them.